Transformation of a Cutaneous Follicle Center Lymphoma to a Diffuse Large B-Cell Lymphoma—An Unusual Presentation - J. Dias Coelho; F. Diamantino; I. Costa; P. Farinha; P. Gameiro; M. Sebastião; J. Baptista (Case Reports in Medicine)
Primary cutaneous follicle center lymphoma (PCFCL) is characterized by a proliferation of follicle center cells in the skin. A definitive diagnosis is frequently delayed because of difficulties in interpretation of the histopathologic findings. It has an excellent prognosis with a 5-year survival over 95% and its risk of transformation has not been established. We describe a case report of man with a gastric diffuse large B-cell lymphoma (DLBCL) referred to our clinic because of nodules in the back that had gradually developed over a period of 10 years. A biopsy performed 3 years before was interpreted as reactive follicular hyperplasia. A new skin biopsy revealed a diffuse large B-cell lymphoma and immunoglobulin heavy chain gene rearrangements from the initial skin biopsy (PCBCL) and the DLBCL gastric biopsy were studied by polymerase chain reaction and an identical clonal rearrangement was detected which was highly suggestive of a transformation lymphoma.